Methylation pattern of THBS1, GATA-4, and HIC1 in pediatric and adult patients infected with helicobacter pylori - Alvarez, Marisa Claudia; Ladeira, Marcelo Sady Placido [UNESP]; Scaletsky, Isabel Cristina Affonso; Pedrazzoli Jr., José; Ribeiro, Marcelo Lima (Springer Nature, 2013)
Background: Helicobacter pylori infection is usually acquired in childhood and persists into adulthood if untreated. The bacterium induces a chronic inflammatory response, which is associated with epigenetic alterations in oncogenes, tumor-suppressor genes, cell-cycle regulators, and cell-adhesion molecules. Aim: The aim of this study was to analyze the effect of H. pylori infection on the methylation status of Thrombospondin-1 (THBS1), Hypermethylated in cancer 1 (HIC1) and Gata binding protein-4 (GATA-4) in gastric biopsy samples from children and adults infected or uninfected with the bacterium and in samples obtained from gastric cancer patients. Methods: The methylation pattern was analyzed with methylation-specific PCR. Results: Our results showed that H. pylori infection was associated with methylation of the promoter regions of the THBS1 and GATA-4 genes in pediatric and adult samples (p < 0.01). HIC1 showed the lowest level of methylation, which was not an early event during gastric carcinogenesis. Conclusions: The results from this study indicate that methylation of THBS1 and GATA-4 occurs in the early stages of chronic gastritis and gastric cancer in association with H. pylori infection; however, in gastric cancer samples, other mechanisms cooperate with the down-regulation of these genes. Methylation of HIC1 may not be the principal mechanism implicated in its down-regulation in gastric cancer samples. © 2013 Springer Science+Business Media New York.
Keywords: Chronic gastritis; Gastric cancer; Helicobacter pylori; Methylation